State-of-the-Art Irradiation Technology for Polymeric Hydrogel Fabrication and Application in Drug Release System - Raza, Muhammad Asim; Jeong, Jin-Oh; Park, Sang Hyun (Frontiers in Materials, 2021)
Chronic and debilitating diseases can be marginally cured by anti-inflammatory, antiseptic, and antibiotic drugs, there is still need for more efficacious delivery approaches. Biodegradable and biocompatible polymeric hydrogels are essential requirements for drug release systems due to sustained or targeted drug delivery. Irradiation crosslinking of polymers is considered a safe route for the fabrication of hydrogels because crosslinking takes place without addition of unnecessary toxic reagents such as initiators or crosslinkers. This technology is a useful way to induce sterilization and crosslinking in a single step. Several natural and synthetic polymers in different combinations are crosslinked through high energy ionizing radiation such as electron beam and gamma ray irradiation. Polymeric hydrogels prepared using these techniques exhibit good gel fraction, swelling ratio, and mechanical properties. In addition, hydrogels possess drug loading and release characteristics, antimicrobial characteristics, and in-vivo/in-vitro cytocompatibility. The advantage of biodegradable and biocompatible drug release systems is the controlled release of drugs without deleterious effects on targeted sites. This mini review about irradiation crosslinked hydrogels will provide sufficient guidelines for new researchers to proceed further in this field.